Ensuring Employee Productivity: Utilizing Job Satisfaction as Mediating - Pinandita, Satria; Soelistya, Djoko; Desembrianita, Eva (MANAZHIM, 2024)
The objective of this study is to analyse the factors that impact employee performance, namely the effect of remuneration and punishment, with satisfaction acting as a mediating factor. The study used a quantitative research methodology, focusing on a population of workers. The sample size consisted of 200 respondents. The research findings indicate that Compensation, Discipline, and Job Satisfaction have a direct and substantial effect on employee performance. Additionally, work discipline positively and significantly influences job satisfaction. However, Compensation does not have a positive and significant impact on Job Satisfaction. The mediation analysis demonstrates that employee satisfaction plays a crucial role in fully mediating the impact of compensation and discipline on employee performance. Therefore, in order to enhance performance, it is imperative to prioritise employee satisfaction in the workplace and also pay close attention to employee compensation and work discipline.